Analisis Penyerapan Tenaga Kerja Pada Usaha Ritel Di Kecamatan Kraksaan - Siti Fajriya; Rashika Nabilatus Sa’adah; Ghefira Mia Rhianti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine labor absorption in the Kraksaan area. This research uses a qualitative approach with a non-probability sampling method. This research concludes that retail businesses have no effect on labor absorption in the Kraksaan area because only a small number of workers are needed in retail businesses. The reason these retail stores do not absorb workers in the Kraksaan area is because retail stores see the seriousness of the way they work and also other reasons. Retail business owners currently lack confidence in the shops they set up, which causes these real businesses to develop less.